2007
DOI: 10.1590/s0100-204x2007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Sistema de previsão da safra de soja para o Brasil

Abstract: Resumo -Este trabalho teve por objetivo avaliar um sistema de previsão de safra de soja para o Brasil, baseado em modelos empíricos regionalizados para estimativa da produtividade, a partir de um banco de dados de área cultivada em escala municipal, e de um sistema de monitoramento agrometeorológico de abrangência nacional. Forecast system of soybean crop yield for BrazilAbstract -The aim of this work was to evaluate a system to forecast soybean crop yield for Brazil, based on regional empirical models to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
21

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 18 publications
1
22
0
21
Order By: Relevance
“…Data from the municipality of Pelotas in 2005 is a possible example (Figure 3). Similar results were reported in Assad et al (2007), when soybean showed high-yield losses in 2005 in this region.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Data from the municipality of Pelotas in 2005 is a possible example (Figure 3). Similar results were reported in Assad et al (2007), when soybean showed high-yield losses in 2005 in this region.…”
Section: Resultssupporting
confidence: 89%
“…One of the changes in this model, if compared to the one cited above, is that yield calculation is updated daily, whenever the system receives new weather data, at the end of each day, similarly to the system developed for soybean by Assad et al (2007) in Brazil. Another difference is the introduced empirical parameter, called adjusted yield response factor (ky*), bellow explained, which results in higher or lower response to water deficit, according to technological specificities related to different production systems, in each yield class.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simpler yield models, as those based mostly on water availability throughout the crop cycle, have also been used to estimate potential and actual yields (Assad et al, 2007;Monteiro et al, 2013), as well as to characterize genotype sensitivity to water deficits (Andrioli & Sentelhas, 2009;Battisti & Sentelhas, 2015). Among these, the FAO method (Doorenbos & Kassam, 1979), which uses a physiologicalmathematical approach, has proved to be robust, since it is based on a conservative relationship between biomass and water use (Hsiao, 1993;Morison et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the production it is necessary to know the cultivated areas with the species of interest and its productivity in different regions (ASSAD et al, 2007). The crops productivity can also be estimated from agrometeorological models (FONTANA et al, 2001).…”
Section: Introductionmentioning
confidence: 99%